Keparahan Karies Gigi dan Kualitas Hidup Harian Anak Ditinjau dari Aspek Gangguan Makan, Bicara, Belajar dan Tidur - Lesmana, Hans; Sitanaya, Rini; Irayani Yunus, Surya; Amalia Rahmat, Yuni (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Dental caries is the most common oral health problem in children and can impact quality of life, especially in eating, speaking, learning, and sleeping activities. The prevalence of childhood caries in Indonesia is still high and requires special attention. This study aims to determine the relationship between the severity of dental caries and the quality of life of children at SDN 5 Benteng, Sidenreng Rappang Regency. This type of study is an observational analytic with a cross-sectional design using a total sampling technique of 70 children in grades 3–5 from a total of 156 students. Caries severity was assessed using the DMFT/deft index according to WHO criteria, while quality of life was measured with a questionnaire covering aspects of eating, speaking, learning, and sleeping disorders. Data analysis was performed univariately, bivariate using the Spearman correlation test, and multivariate with logistic regression. The results showed that most children experienced very high caries severity (41.4%) with the dominant quality of life disturbance in the eating aspect (58.6%). Bivariate testing showed a significant association between caries severity and eating disorders (p=0.013; OR=2.15), but no significant association with speech (p=0.339), learning (p=0.309), or sleep (p=0.379) disorders. The conclusion of this study is that the severity of dental caries is significantly associated with children's quality of life, particularly in terms of eating disorders. However, there was no significant association between speech, learning, and sleep. Efforts to prevent dental caries through education, regular checkups, and promotional programs in schools need to be increased to support children's dental health and quality of life. Keywords: Dental caries; eating disorders; speech; learning; sleep